4-Methoxydalbergione Inhibits Bladder Cancer Cell Growth via Inducing Autophagy and Inhibiting Akt/ERK Signaling Pathway - Du, Haifang; Tao, Ting; Xu, Simeng; Xu, Changqiong; Li, Shan; Su, Qiongli; Yan, Jing; Liu, Bo; Li, Ran (Frontiers in Molecular Biosciences, 2022)
Bladder cancer (BC) ranks the fourth in incidence in cancers of men and is a common malignant tumor in women. 4-Methoxydalbergione (4MOD), which is purified from Dalbergia sissoo Roxb, has been shown to have anticancer capacity for osteosarcoma and astroglioma. The role of 4MOD in bladder cancer has not been investigated. This study aims to evaluate the anticancer effect of 4MOD in BC cells and its possible mechanisms. The two human bladder cancer cell lines J82 and UMUC3 were used to evaluate the proliferation inhibitory effect of 4MOD by CCK8 and clonogenic assays. The migratory and invasive ability of tumor cells was examined by scratch test and transwell assay. Apoptosis was detected by flow cytometry and TUNEL assays. The autophagy-related molecules including Beclin-1 and LC3 were examined by Western blotting analysis. Furthermore, the RT-PCR was used to detect the mRNA expression of LC3. 4MOD repressed cell proliferation, migration, invasion and induced cell apoptosis in a concentration-dependent manner. The IC50 values of J82 and UMUC3 were 8.17 and 14.50 μM respectively. The mRNA and protein expression ratio of light chain 3-II (LC3-II)/LC3-I and the protein expression of Beclin-1 were increased when the BC cells were treated with 4MOD. The treatment of 4MOD attenuated the phosphorylation of Akt and ERK in the BC cells. We revealed that the 4MOD inhibits BC cells growth by inducing autophagy and inhibiting Akt/ERK signaling pathway. Our study provides new insights into the mechanism by which 4MOD weakens the proliferation of BC cells. This study demonstrates that 4MOD provided a lead compound for the development of novel compound with potent anticancer effect on BC cells.